2000
DOI: 10.1073/pnas.230442897
|View full text |Cite
|
Sign up to set email alerts
|

Paired Ig-like receptor homologs in birds and mammals share a common ancestor with mammalian Fc receptors

Abstract: Paired Ig-like receptors (PIR) that can reciprocally modulate cellular activation have been described in mammals. In the present study, we searched expressed sequence tag databases for PIR relatives to identify chicken expressed sequence tags predictive of Ϸ25% amino acid identity to mouse PIR. Rapid amplification of cDNA ends (RACE)-PCR extension of expressed sequence-tag sequences using chicken splenic cDNA as a template yielded two distinct cDNAs, the sequence analysis of which predicted protein products wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 58 publications
2
67
0
Order By: Relevance
“…Initially, the CHIR genes have been isolated by using homology searches with mouse PIR-B probes in the chicken EST database (20). Reciprocally mouse PIR-B itself was cloned in an attempt to find a homologue of the human Fc␣RI (CD89) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the CHIR genes have been isolated by using homology searches with mouse PIR-B probes in the chicken EST database (20). Reciprocally mouse PIR-B itself was cloned in an attempt to find a homologue of the human Fc␣RI (CD89) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Design, Construction, and Expression of bFc␥2R MutantsBovine Fc␥2R is a member of the Ig gene superfamily of proteins and is closely related to several human members of this family, including the KIRs, Ig-like transcripts, and the human Fc␣R (CD89) (14). Several three-dimensional structures of KIR proteins have now been described, thus identifying the secondary structure composition of the Ig domains.…”
Section: Panel F)mentioning
confidence: 99%
“…The genes of the LRC are only slightly less closely related genetically to the other mammalian FcRs than they are to each other. Moreover, available crystal data suggest that proteins encoded in the LRC are structurally quite similar to FcRs (Fc␥RII, III, and Fc⑀RI) (14). However, despite this high degree of homology, the location of the ligand binding sites within these molecules varies considerably.…”
Section: Fig 2 Alignment Of the Protein Sequences Of Bfc␥2r And P58mentioning
confidence: 99%
See 1 more Smart Citation
“…3). Dennis et al (2000) have originally suggested that Fc and LRC sequences share a common ancestor. These authors have pointed out that, despite the low degree of sequence similarity, the tertiary structures of the Ig-like domains encoded by the FcγRIIB (D2 of group FcII in Fig.…”
mentioning
confidence: 99%